Multi-Stage Expansion Planning of Distribution Network Considering Distributed Power Generation - Wang, Qingjie; Ma, Jing; Wang, Hongxia (Frontiers in Energy Research, 2022)
Abstract: With the gradual increase in the penetration rate of distributed power sources, in view of the planning problem of coordinating the location and capacity of distributed power sources with the grid frame and transformers of the distribution network, a distribution network that takes into account distributed power sources is proposed. Aiming at the lowest cost of investment, maintenance, energy production, energy loss, and load loss penalty, and considering the power flow constraints, planning and operation constraints of each planning stage, a multi-stage expansion planning model for the distribution network is established. The mixed-integer linear programming algorithm is used to solve the problem, and the optimal planning scheme at each stage is obtained. The simulation results show that the multi-stage expansion planning method for coordinating distributed power and distribution network proposed in this paper can prevent the problems of isolated nodes and transmission nodes, improve the reliability of the planning scheme, and have good economic benefits.